Acute Toxicity Test of Unripe Papaya (Carica papaya L.) Aqueous Extract (UPAE) on The Blood Urea and Creatinine Concentration - Yuktiana Kharisma; Yuke Andriane; Titik Respati (Global Medical & Health Communication (GMHC), 2018)
Unripe papaya aqueous extract (UPAE) widely used as lactation stimulator, antidiabetes, antibacterial, and anti-inflammatory. The utilization of papaya is not known for its safety yet, so it is necessary to research its toxicity. The purpose of this study was to investigate the acute toxicity of UPAE on renal function through measurement of blood urea and creatinine levels. This study was conducted in July 2017 in Laboratory of Medical Biology, Faculty of Medicine, Universitas Islam Bandung. This study used pure in vivo experimental design on 11 Swiss Webster mice using the dose of acute toxicity determination based on new recommended methods of 0; 50; 200; 400; 800; 1,000; 1,500; 2,000; 3,000; 4,000; and 5,000 mg/kgBW. After 24 hours, 1 mL blood drawn through the tail examined for blood urea and creatinine levels. The measurement of urea content using kinetic method point and creatinine level using modified Jaffe method. Provision of UPAE at doses of 0, 50, 200, 400, 800, and 1,000 mg/kgBW resulted on blood urea equal to 39, 35, 48, 49, 48, and 32 mg/dL respectively. Blood urea level 23, 22, 28, 34, and 35 mg/dL was obtained at 1,500 UPAE doses; 2,000; 3,000; 4,000; and 5,000 mg/kgBW dosages respectively. After 24 hours of UPAE administration, the creatinine level in various doses using new recommended method of (0–5,000 mg/kgBW) were 0.75, 0.54, 0.53, 0.50, 0.60, 0.54, 0.52, 0.55, 0.42, 0.51, and 0.40 mg/dL. In conclusion, UPAE do not cause acute toxicity on renal function through measurement of blood urea and creatinine levels. TOKSISITAS AKUT EKSTRAK AIR BUAH PEPAYA (CARICA PAPAYA L.) TERHADAP KADAR UREUM DAN KREATININ DARAHEkstrak air buah pepaya muda (EABPM) digunakan secara empiris sebagai laktagogum, antidiabetes, antibakteri, dan antiinflamasi. Tingkat keamanannya belum banyak diketahui sehingga perlu dilakukan penelitian uji toksisitas akut. Tujuan penelitian ini adalah mengetahui toksisitas akut EABPM terhadap fungsi ginjal melalui pengukuran kadar ureum dan kreatinin plasma. Penelitian ini dilaksanakan pada bulan Juli 2018 di Laboratorium Biologi Medis, Fakultas Kedokteran, Universitas Islam Bandung. Penelitian ini menggunakan desain eksperimental murni in vivo terhadap 11 ekor mencit betina galur Swiss Webster dengan penentuan dosis sesuai dengan new recommended method: 0, 50, 200, 400, 800, 1.000, 1.500, 2.000, 3.000, 4.000, dan 5.000 mg/kgBB. Setelah 24 jam, diambil darah melalui ekor mencit sebanyak 1 mL untuk diperiksa kadar ureum dan kreatinin plasma. Pengukuran kadar ureum menggunakan point kinetic method dan kadar kreatinin menggunakan metode Jaffe yang dimodifikasi. Pemberian EABPM pada dosis 0, 50, 200, 400, 800, dan 1.000 mg/kgBB didapatkan kadar ureum plasma 39, 35, 48, 49, 48, dan 32 mg/dL secara berurutan. Kadar ureum plasma 23, 22, 28, 34, dan 35 mg/dL didapatkan pada pemberian dosis EABPM sebanyak 1.500, 2.000, 3.000, 4.000, dan 5.000 mg/kgBB. Kadar kreatinin plasma dalam berbagai dosis (0–5.000 mg/kgBB) adalah 0,75; 0,54; 0,53; 0,50; 0,60; 0,54; 0,52; 0,55; 0,42; 0,51; dan 0,40 mg/dL. Simpulan, EABPM tidak menimbulkan tanda toksisitas akut pada fungsi ginjal melalui pengukuran kadar ureum dan kreatinin plasma.